2012
DOI: 10.1109/tdei.2012.6259979
|View full text |Cite
|
Sign up to set email alerts
|

Surface charging of silicondioxide/silicon structures

Abstract: The surface of silicondioxide/silicon structures is charged with the tip of a cantilever in contact mode by application of a voltage. Then, the surface potential is measured contactless using the Kelvin option of an atomic force microscope. On the position of the charged domain a potential difference in relation to the uncharged region is found. It turns out that the height and the width of this potential difference depend on the charging time, on the height of the charging voltage, on the sample thickness, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 37 publications
0
3
0
Order By: Relevance
“…In particular, KPFM is powerful to study surface work function, [18][19][20] band bending and interfacial dipole, [21][22][23][24][25] and also employed to quantitatively evaluate charge quantity trapped in insulators. [26][27][28][29][30] In this report, KPFM is used to simulate programming/ erasing process and directly profile charge trapping into the nano-floating-gate in a pentacene-based OFET nonvolatile memory. It is demonstrated that the integration of surface potential change (DW) after programming/erasing reflects the quantity of electron/hole trapping.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In particular, KPFM is powerful to study surface work function, [18][19][20] band bending and interfacial dipole, [21][22][23][24][25] and also employed to quantitatively evaluate charge quantity trapped in insulators. [26][27][28][29][30] In this report, KPFM is used to simulate programming/ erasing process and directly profile charge trapping into the nano-floating-gate in a pentacene-based OFET nonvolatile memory. It is demonstrated that the integration of surface potential change (DW) after programming/erasing reflects the quantity of electron/hole trapping.…”
mentioning
confidence: 99%
“…N 2 gas was flowed in the measuring chamber to maintain a low humidity ($20%), as humidity may influence surface charge diffusion. 26,28 The KPFM instrument was operated in the Peak Force tapping mode, 33 with scanner oscillation frequency f 0 of 2 kHz and amplitude of 150 nm. This offers a precise force control between the probe and sample surface and allows non-destructive potential probing on soft materials such as organic thin films, preserving their surface morphology during scanning.…”
mentioning
confidence: 99%
“…There are two main factors for piezoresistive pressure sensor chips that affect the useful signal and errors. The first factor is related to leakage currents of pressure sensor chip due to the limiting ability of closing the p-n junction for high and low-alloyed regions of piezoresistors (PRs) on wafers with single-crystal structure [24][25][26][27], defectivity [28] and embedded charge in the surface silicon oxide [29], and due to the effect of the difference in the temperature coefficient of expansion (TCE) between aluminum (or other metal) and silicon on the thin membrane structure [30][31][32]. The second factor is the relaxation of residual mechanical stresses (RMS) in the micro-assembly structure of pressure sensor chip [33][34][35][36][37].…”
Section: Introductionmentioning
confidence: 99%